TRAJECTORIES OF BLACK WOMEN IN HIGHER EDUCATION: BARRIERS, ACHIEVEMENTS AND WAYS FORWARD - Aguiar, Marcela; da Silva, Gustavo Simas (Seven Editora, 2025)
This article maps and analyzes the trajectories of black women in Brazilian higher education from an intersectional perspective of race, gender, class and regionality. Based on a narrative literature review, it examines academic studies, institutional reports and statistical data collected from databases such as SciELO, the CAPES Journal Portal, Ipea, IBGE and ENAP. The results show structural barriers (unequal access and permanence), institutional barriers (under-representation in the teaching staff, low effectiveness of quotas in competitive examinations) and symbolic barriers (veiled racism, epistemicide, misogyny, tokenism), which also impact on the mental health of these students and teachers. At the same time, strategies of resistance are identified - such as writing for a living, epistemic aquilombamento and anti-racist pedagogies - which promote the production of counter-hegemonic knowledge, diversify curricula and strengthen support networks. The study highlights recent achievements: the expansion of enrolment following Law 12.711/2012, the entry of the first generation of black female doctors in previously inaccessible areas and the multiplier effects of representation that raise student self-esteem and pluralize science. Finally, practices and policies that are essential for consolidating progress are discussed: expanding affirmative action in admission, tenure and teaching careers; full inclusion of Laws 10.639/2003 and 11.645/2008; institutional recognition of mentoring and extension work; and strengthening black women's collectives as spaces for intellectual production. The conclusion is that the presence of these women moves historically exclusionary academic structures, but substantive equality depends on the articulation between robust public policies and the continuity of insurgent practices led by black intellectuals.DOI: https://doi.org/10.56238/sevened2025.026-023